Fully developed relativistic turbulence - Calzetta, Esteban Adolfo (2021)
We use a simple model consisting of energy-momentum tensor conservation and a Maxwell-Cattaneo equation for its viscous part to study nonlinear phenomena in a real relativistic fluid. We focus on new types of behavior without nonrelativistic equivalents, such as an entropy cascade driven by fluctuations in the tensor degrees of freedom of the theory. We write down the von Kármán-Howarth equations for this kind of turbulence and consider the correlations corresponding to fully developed turbulence.